Migracja zarobkowa - problem społeczny czy indywidualny? Propozycja analizy porównawczej = Labour migration - social or individual problem? The proposal of comparative analysis - Bochno, Ireneusz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
In the article I emphasise significant disagreement in the assessment of the labour migration phenomenon. My objective is to justify the need for comparative analysis of the different perspectives (highlighted and outlined here) on the problem related mainly to the young generation of Poles. In public discourse migration is defined both as a social problem and an individual problem of people who decide to leave the country.
Keywords: migracja zarobkowa; analiza porównawcza; problemy indywidualne; problemy społeczne